Association Between Health-Related Physical Fitness and Depressive Symptoms in Chinese Adolescents: A Nationwide Cross-Sectional Study Under the Healthy China Initiative - Cao YB (Neuropsychiatric Disease and Treatment)
Yu-Bo Cao Beijing Open University, Beijing, People’s Republic of ChinaCorrespondence: Yu-Bo Cao, Email canouzhaoyingzh@163.comObjective: This study explores the relationship between health-related physical fitness and depressive states in adolescents and examines the influence of gender, age, and parental education.Methods: A stratified and cluster sampling method selected 689 students (grades 7, 8, 10, and 11) from a Beijing middle school. After screening, 441 adolescents (12– 18 years, 55.3% male) were included. Measurements included body composition (BMI), cardiopulmonary fitness (vital capacity), muscular strength/endurance (grip strength, sit-ups, standing long jump), and flexibility (sit-and-reach). Depressive states were assessed using the depression subscale of the Achenbach Youth Self-Report Scale (YSR). Data were analyzed using SPSS 24.0 with descriptive statistics, stratified analysis, and Pearson correlation.Results: Cardiopulmonary fitness was significantly negatively correlated with depressive states (r = − 0.346, p < 0.001), while grip strength showed a weak positive correlation with depression (r = 0.137, p = 0.003). Standing long jump exhibited a slight positive correlation with depression scores (r = 0.114, p < 0.05), but the effect size was negligible. BMI, sit-ups, and sit-and-reach showed no significant correlation with depression scores (p > 0.05). Stratified analysis revealed that females aged 15– 18 had significantly higher depression scores than their male counterparts (p < 0.001) and were negatively correlated with cardiopulmonary fitness (r = − 0.32, p = 0.002). Grip strength in males significantly increased with age (r = 0.62, p < 0.001), while in females, it stabilized after age 15 and showed no significant correlation with depression (p > 0.05).Conclusion: Cardiopulmonary fitness is a key factor in adolescent mental health, with a stronger impact than muscular strength. Late-adolescent females are at higher depression risk, likely due to lower cardiopulmonary fitness and increased stress. Findings highlight the need for interventions improving cardiopulmonary fitness to support adolescent mental health.Keywords: healthy China perspective, adolescents, health-related physical fitness, depression-related states, empirical study, correlation analysis